Pitfall trap design affects the capture efficiency of harvestmen (Opiliones) and millipedes (Diplopoda) - Stašiov, Slavomír; Čiliak, Marek; Wiezik, Michal; Svitok, Marek; Wieziková, Adela; Diviaková, Andrea (Ecology and evolution, 2021)
Pitfall trapping is one of the standard methods used for the capture of ground-active arthropod groups. Despite being frequently used, the standardization of this method is problematic due to the large range of combinations of the individual parameters of pitfall traps with varying efficacy under different environmental conditions. We evaluated the effects of the trap diameter, the fixing fluid, and their combination on the capture efficacy for harvestmen (Opiliones) and millipedes (Diplopoda). We used pitfall traps with three different diameters: 3 cm, 5 cm, and 12 cm, filled with three types of fixing fluids (saturated fluid of NaCl, 10:1 mixture of 70% ethanol and glycerol and 4% formaldehyde). Altogether, 90 traps representing nine combinations of trap diameters and fixing fluid were placed on a mown meadow in spring and autumn intervals for a total of 45 days. We sampled 1,488 individuals representing 11 harvestmen species and 881 individuals representing 11 millipede species. Large (d = 12 cm) and medium (5 cm) traps captured significantly more millipede species and individuals than the small-sized traps (3 cm). The same effect was observed for harvestmen species richness, whereas the medium traps (d = 5 cm) captured the highest mean activity of harvestmen. By analyzing the differences in the body sizes of the studied arthropods in relation to the trap diameter and fluid, we found that larger traps, as well as traps filled with NaCl solution, captured larger harvestmen more frequently than the other trap types. Our results revealed that the combination of larger traps (d = 5 and 12 cm) and formaldehyde was most effective in the capture of both studied groups. However, the disadvantage of formaldehyde is its toxicity.
Keywords: fixing fluid; trap diameter; method selection; capture rate; body size